Side effects of aminoglycosides on the kidney, ear and balance in cystic fibrosis. Issue 7 (13th July 2010) - Prayle, Andrew; Watson, Alan; Fortnum, Heather; Smyth, Alan
Abstract : Aminoglycoside antibiotics are a central component of the treatment of pulmonary exacerbations of cystic fibrosis (CF) and slow the decline in lung function which ultimately causes the death of most patients. The prognosis of CF has improved, and thus side effects of treatments have become increasingly important. Observational studies suggest that the morbidity from side effects of aminoglycosides is disturbingly common, and that aggressive treatment may lead to more side effects. This review of the current literature on side effects of aminoglycosides considers the pathophysiological mechanisms, epidemiology and risk factors, investigation of side effects and preventative strategies. Treatments which have shown early promise are identified and areas of future research are discussed.